Decreased Compressional Sound Velocity Is an Indicator for Compromised Bone Stiffness in X-Linked Hypophosphatemic Rickets (XLH) - Raimann, Adalbert; Mehany, Sarah N.; Feil, Patricia; Weber, Michael; Pietschmann, Peter; Boni-Mikats, Andrea; Klepochova, Radka; Krššák, Martin; Häusler, Gabriele; Schneider, Johannes; Patsch, Janina M.; Raum, Kay (Frontiers in Endocrinology, 2020)
Objectives: To assess the diagnostic potential of bidirectional axial transmission (BDAT) ultrasound, and high-resolution peripheral quantitative computed tomography (HR-pQCT) in X-linked hypophosphatemia (XLH, OMIM #307800), a rare genetic disorder of phosphate metabolism caused by mutations in the PHEX gene. Methods: BDAT bone ultrasound was performed at the non-dominant distal radius (33% relative to distal head) and the central left tibia (50%) in eight XLH patients aged between 4.2 and 20.8 years and compared to twenty-nine healthy controls aged between 5.8 and 22.4 years. In eighteen controls, only radius measurements were performed. Four patients and four controls opted to participate in HR-pQCT scanning of the ultradistal radius and tibia. Results: Bone ultrasound was feasible in patients and controls as young as 4 years of age. The velocity of the first arriving signal (νFAS) in BDAT ultrasound was significantly lower in XLH patients compared to healthy controls: In the radius, mean νFAS of XLH patients and controls was 3599 ± 106 and 3866 ± 142 m/s, respectively (−6.9%; p < 0.001). In the tibia, it was 3578 ± 129 and 3762 ± 124 m/s, respectively (−4.9%; p = 0.006). HR-pQCT showed a higher trabecular thickness in the tibia of XLH patients (+16.7%; p = 0.021). Conclusions: Quantitative bone ultrasound revealed significant differences in cortical bone quality of young XLH patients as compared to controls. Regular monitoring of XLH patients by a radiation-free technology such as BDAT might provide valuable information on bone quality and contribute to the optimization of treatment. Further studies are needed to establish this affordable and time efficient method in the XLH patients.